Fecal CEA Has an Advantage in the Diagnosis of Colorectal Cancer at Early Stage - Linfang Li MD; Shan Xing MD; Miantao Wu MD; Yufeng Ao MD; Xin Zheng MD; Rongzeng Cai MD; Runkun Han MD; Jingcong Li MD; Xiaohui Li MD; Qiuyao Zeng MD (Cancer Control, 2021)
Purpose Serum carcinoembryonic antigen (SCEA) level is often measured in patients with CRC but suffers from poor sensitivity and specificity as a diagnostic biomarker. CEA is more abundant in stool than in serum, but it has not been widely studied. This study aimed to elucidate the efficacy of fecal CEA (FCEA) as a potential non-invasive biomarker for early diagnosis of CRC. Materials and Methods We retrospectively analyzed the determination of FCEA and SCEA levels by electrochemiluminescence. We evaluated the diagnostic accuracy of FCEA and SCEA levels in early-stage CRC patients and healthy controls using ROC curve. Results A total of 298 people were included: 115 patients with CRC, 35 patients with adenomatous polyp (APC), 46 patients with non-gastrointestinal cancer (NGC), and 102 healthy controls (HC). The FCEA concentrations in CRC and APC patients were significantly higher than that of NGC and HC, and this is different from SCEA expression in APC and NGC. As a diagnostic biomarker of CRC, FCEA had significantly larger AUC compared with SCEA (.802 vs .735, P   < .001). For identifying early-stage colorectal cancer, FCEA showed better diagnostic efficacy (AUC: .831) than SCEA (AUC: .750), and the combination of the 2 biomarkers was even higher (AUC: .896). The sensitivity of FCEA was higher than that of SCEA (78.7% vs 29.8%). When SCEA was negative, 80.3% of CRC and 54.6% of APC cases could be identified by FCEA. Conclusion Compared with SCEA, FCEA has more advantages in the diagnosis of the early stage of colorectal cancer and adenomatous polyps.